Molecular identification of cellulase and protease producing Bacillus tequilensis UTMSA14 isolated from the geothermal hot spring in Lau Sidebuk Debuk, North Sumatra, Indonesia - Edy Fachrial; Raden Roro Jenny Satyo Putri; I Nyoman Ehrich Lister; Sari Anggraini; Harmileni HARMILENI; Titania T. Nugroho; Saryono SARYONO (Society for Indonesian Biodiversity, 2020)
Abstract. Fachrial E, Putri RRJS, Lister INE, Anggraini S, Harmileni, Nugroho TT, Saryono. 2020. Molecular identification of cellulase and protease producing Bacillus tequilensis UTMSA14 isolated from the geothermal hot spring in Lau Sidebuk Debuk, North Sumatra, Indonesia. Biodiversitas 21: 4719-4725. The industrial need for stable microbial enzymes tends to increase every year. The aim of this study was to isolate and identify the protease and cellulase producing thermophilic bacteria isolated from the geothermal spring of Lau Sidebuk Debuk, North Sumatra, Indonesia. The protease activity was determined based on the formation of halo zone on Skim Milk Agar, while cellulase was confirmed using CMC plate agar method. Nine bacterial isolates were successfully obtained from the sediments and water, and both activities were observed in only one isolate, known as UTMSA14. These isolates were characterized biochemically and morphologically. The molecular identification of UTMSA14 was done by 16S rRNA sequencing based on BLAST and phylogenetic analysis using MEGA X. Phylogenetic analysis showed that UTMSA14 clustered together with Bacillus tequilensis strain 10b (accession number NR_104919.1), which ascertained the isolate as Bacillus tequilensis strain 10b (accession number NR_104919.1). This is the first report of a thermophilic bacteria isolated from Lau Sidebuk Debuk hot springs, with the ability to produce cellulase and protease. further research is needed to purify and characterize the resulting enzymes, with a potential for industrial applications.